2022
DOI: 10.1177/03795721221119249
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders, Relationships, and Coordination: 2015 Baseline Study of Needed Enablers for Bridging Agriculture-Nutrition Gaps in Nigeria

Abstract: Background: Renewed efforts by the Nigerian government to address malnutrition have led to nutrition actions by several sectors, including the agriculture sector. However, the success of these actions depends on the characteristics of the stakeholders involved, including their relationships and coordination. Objective: This article reports a 2015 study of nutrition-sensitive agricultural stakeholders in Nigeria that assessed what the stakeholders do, where they work and how they are organized to improve nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In the 2015 situation analysis, the IANWG was reported as a key structure for effective NSA actions and coordination. 23 Yet, the IANWG experienced multiple long periods of inactiveness despite efforts to keep it operational. Hence, a study, which is reported in this special issue, 39 was conducted in 2018 to identify approaches for sustaining the activities of the IANWG.…”
Section: Implementation Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…In the 2015 situation analysis, the IANWG was reported as a key structure for effective NSA actions and coordination. 23 Yet, the IANWG experienced multiple long periods of inactiveness despite efforts to keep it operational. Hence, a study, which is reported in this special issue, 39 was conducted in 2018 to identify approaches for sustaining the activities of the IANWG.…”
Section: Implementation Researchmentioning
confidence: 99%
“…The already mentioned IANWG was established as the primary coordination mechanism for NSA within FMARD and between FMARD and other ministries, departments, and agencies (MDAs) for the purposes of policy coherence, consistency, and synergy. In the Special Issue, Adeyemi et al 23 highlight the various coordination mechanisms that exist for different purposes, while Ezekannagha et al 39 describe the IANWG and its challenges and prospects. Overall, the FMARD needs to continue to actively participate in national coordination structures such as the National Committee on Food and Nutrition and the National Council on Nutrition.…”
Section: Multisectoral Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, both food security and nutrition were assumed to be natural dividends of agricultural development. 8,9 Yet, due to decades of underinvestment, Nigeria became a net food and raw material importing country. The increasing global calls for nutrition-sensitive agriculture (NSA) coincided with reforms in the agriculture sector, and the Federal Government of Nigeria, from about 2010, began to take strategic steps to maximize the potential for agriculture to improve nutrition.…”
Section: Introductionmentioning
confidence: 99%